Violation of socialization of the individual in the paradigm of christian-oriented psychotherapy - Matejko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with mental dependency Rights paradigm of Christian-oriented psychotherapy, where addiction appears as a passion, moral flaw, a disease of the human soul. We give a comparative analysis of formation mechanisms of addictive behavior in traditional and Christian- oriented approaches. Submitted main passions specific person proved that indulging his passions, people are paying their own health. The scope of the Christian-oriented psychotherapy is the spiritual and moral component of human behavior, understanding the relationship of sin and disease, integrity and health.